Voice Powered Task Automation Using AI - Smit Makodia; Darshana Patel; Aditiba Jadeja; Soniya Aghera; Darshana Bhatti; Vijaysinh Jadeja (Utilitas Mathematica, 2024)
In many developing regions, including India, the demand for scalable and intuitive automation solutions is growing rapidly. Traditional robotic systems often require complex programming knowledge, creating a barrier for non-expert users.In response to the growing need for scalable, voice-driven automation, a platform named CATALYST needs to be considered. It serves as a voice-to-action bridge, acting as a smart link and translating natural language commands into executable robotic actions. It completely gets rid of the complex programming setups by employing user spoken commands. Without any training, the system changes the human language to the sequential robotic executions.One step further in this direction is the LLM (Large Language Model) processing, speech to text services, and n8n (workflow automation) which altogether make the just mentioned system. The demonstration of the system was the use of a virtual car which was under the control of a virtual microcontroller. The research results state that CATALYST is able to perform prompt planning and task processing, having short voice processing times as well as robot execution times being of a predictable nature. This development can make the interaction between humans and robots more user-friendly and time-saving in different sectors.